Low diagnostic and predictive value of anti-dsDNA antibodies in unselected patients with recent onset of rheumatic symptoms: results from a long-term follow-up Scandinavian multicentre study. (August 2013) - Compagno, M; Jacobsen, S; Rekvig, OP; Truedsson, L; Heegaard, NH; Nossent, J; Jönsen, A; Jacobsen, RS; Eilertsen, GØ; Sturfelt, G; Bengtsson1, AA
<x xml:space="preserve">Abstract</x> Objectives: To verify the diagnostic accuracy of anti-double-stranded DNA (anti-dsDNA) antibodies detected by the Crithidia luciliae immunofluorescence test (CLIFT) in a cohort of unselected patients, referred to a rheumatologist due to recent onset of rheumatic symptoms. Method: A total of 1073 consecutive patients were screened for anti-nuclear antibodies (ANAs). Serum samples from 292 ANA-positive and 292 matching ANA-negative patients were tested three times for anti-dsDNA antibodies, using two different CLIFT kits (ImmunoConcepts® and Euroimmun®). An initial clinical diagnosis was made by rheumatologists unaware of the results. The diagnoses were updated after a median follow-up of 4.8 years. Results: CLIFT was positive at least once in 60 patients but only 23 patients were CLIFT positive in all of the assays. Diagnosis of systemic lupus erythematosus (SLE) was made initially in 65 patients, of whom 24 (37%) were CLIFT positive. Many other diagnoses were observed among the CLIFT-positive patients. Overall, 16 (5.5%) ANA-negative patients were CLIFT positive. After approximately 5 years, the diagnosis of SLE remained unchanged in 63 patients (23 CLIFT positive) and altered in only two (one CLIFT positive). Among the 36 CLIFT-positive patients who were not diagnosed with SLE at study entry, only one developed SLE during the follow-up period. Conclusions: CLIFT was not reliable as a diagnostic tool in unselected patients with rheumatic symptoms. ANAs were of little value as a screening test before the CLIFT analysis. CLIFT had surprisingly low positive predictive value (PPV) for the diagnosis of SLE despite its high specificity. For non-SLE patients, being CLIFT positive poses little risk of developing SLE within 5 years.